Nuclear Position and Shape Deformation of Chromosome 8 Territories in Pancreatic Ductal Adenocarcinoma - Sylvia Timme; Eberhard Schmitt; Stefan Stein; Jutta Schwarz-Finsterle; Jenny Wagner; Axel Walch; Martin Werner; Michael Hausmann; Thorsten Wiech (Analytical Cellular Pathology)
Cell type specific radial positioning of chromosome territories (CTs) and their sub-domains in the interphase seem to have functional relevance in non-neoplastic human nuclei, while much less is known about nuclear architecture in carcinoma cells and its development during tumor progression. We analyzed the 3D-architecture of the chromosome 8 territory (CT8) in carcinoma and corresponding non-neoplastic ductal pancreatic epithelium. Fluorescence-in-situ-hybridization (FISH) with whole chromosome painting (WCP) probes on sections from formalin-fixed, paraffin wax-embedded tissues from six patients with ductal adenocarcinoma of the pancreas was used. Radial positions and shape parameters of CT8 were analyzed by 3D-microscopy. None of the parameters showed significant inter-individual changes. CT8 was localized in the nuclear periphery in carcinoma cells and normal ductal epithelial cells. Normalized volume and surface of CT8 did not differ significantly. In contrast, the normalized roundness was significantly lower in carcinoma cells, implying an elongation of neoplastic cell nuclei. Unexpectedly, radial positioning of CT8, a dominant parameter of nuclear architecture, did not change significantly when comparing neoplastic with non-neoplastic cells. A significant deformation of CT8, however, accompanies nuclear atypia of carcinoma cells. This decreased roundness of CTs may reflect the genomic and transcriptional alterations in carcinoma.